ON THE PERIODS OF RV TAU STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
On the base of GCVS (General Catalogue of Variable Stars) sampling has been carried out the analysis of periods of RV Tau stars (87 RV Tau stars with the known periods). We have given an interpretation of the histogram of periods distribution of these stars on the base of mode composition. All the peaks were identified as a fundamental period, its first, second and other overtones and their harmonics. It was proposed a new classification of these variable stars according to their mode identifications.